On the Way to Mars—Flagellated Algae in Bioregenerative Life Support Systems Under Microgravity Conditions - Häder, Donat‑P. (Frontiers in Plant Science, 2020)
For long-term manned interplanetary missions it is not feasible to carry the necessary oxygen, food, and water to sustain the astronauts. In addition, the CO2 exhaled by the astronauts has to be removed from the cabin air. One alternative is to utilize photosynthetic organisms to uptake the CO2 and produce oxygen. In addition to higher plants, algae are perfect candidates for this purpose. They also serve to absorb wastes and clean the water. Cyanobacteria can be utilized as food supplement. Early ground-based systems include micro-ecological life support system alternative, closed equilibrated biological aquatic system, and the Biomass Production Chamber. The AQUARACK used the unicellular flagellate Euglena which produced the oxygen for fish in a connected compartment. A number of bioregenerative systems (AQUACELLS, OMEGAHAB) have been built for experiments on satellites. A later experiment was based on a 60-ml closed aquatic ecosystem launched on the Shenzhou 8 spacecraft containing several algae and a small snail living in adjacent chambers. Recently the Eu : CROPIS mission has been launched in a small satellite within a Deutschen Zentrum für Luft- und Raumfahrt (DLR) program. In addition to tomato plants, Euglena is included as oxygen producer. One new approach is to recycle urine on a bacterial filter to produce nitrogen fertilizer to grow vegetables.